ANALISIS PERBANDINGAN RISIKO SAHAM SEBELUM DAN SAAT KRISIS PANDEMIC COVID19 PADA TAHUN 2020 (STUDI KASUS: HARGA PENUTUPAN SAHAM PERBANKAN YANG TERGABUNG DALAM INDEKS LQ45) - Gusti Alit Suputra (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Risk can be described as a state of uncertainty of results due to unexpected events. This unexpected event can arise from various sources, such as losses due to stock price movements due to the spread of the Covid19 virus. This research aims to determine whether there is a significant difference between the risk of shares before and when the Covid19 of 2020 occurs in banking stocks that are included in the LQ45 index. This research uses the statistical test method with the analysis technique of two difference test (paired t-test ). The research results have proven that based on the test results at the real level (Î±) = 5% through the paired t-test, it can be seen that there is a significant difference between the risk of stocks before and when the Covid19 virus spread in 2020. on banking stocks that are included in the LQ45 index. This difference can be seen from the Sig (2-tailed) value of 0,000. Meanwhile, the mean value turned out to produce a pre-crisis value, namely 52.961 408684 and during the crisis, namely 38.275236981. This means that the average risk during the crisis is smaller than before the crisis. This is because the stocks under study are part of the LQ45 index or stocks that have higher liquidity than other stocks. So that the phenomenon of the global crisis may not really affect the four banking companies, namely BCA, Danamon, Mandiri and BRI. This research is expected to become a reference for Indonesian financial institutions, especially for banks with regard to several variables that can impact the decision to choose stocks so that financial performance can be improved.